Mechanism Of Dual-Function Srna Smbf7 Regulating Streptococcus Mutans Biofilms - Li, Jing (International dental journal, 2025)
To investigate the role and mechanism of the riboregulatory target mRNA and peptide regulation functions of the dual-function sRNA SmbF7 of Streptococcus mutans in biofilm formation. The wild-type strain was Streptococcus mutans UA159, the medium used was BHI, and the animal experiments have been ethically approved. The research was conducted through experiments including the construction of the Streptococcus mutans SmbF7 mutant, monitoring growth curves, crystal violet staining, anthrone sulfuric acid colorimetric method, scanning electron microscopy, site-directed mutagenesis, RNA mutation, in vitro transcription of RNA, qRT-PCR, target mRNA validation, transcriptomics, proteomics, and the rat caries model. All experiments were repeated at least three times, and the data obtained were statistically analyzed using one-way ANOVA in SPSS 25.0. P < 0.05 indicates that the difference is statistically significant. After overexpressing SmbF7, Streptococcus mutans's growth was slowed down, and the biofilm was significantly reduced. Through transcriptome and target gene prediction, 11 intersecting and overlapping target mRNAs of SmbF7 were screened to exert ribose regulatory functions. The sORF-encoded peptide in SmbF7 was the toxin Fst of the type I TA system, and molecular docking simulations revealed the binding potential between the peptide Fst and the biofilm-associated protein GTFB. SmbF7 has a dual regulatory role, it can be used as a base-paired sRNA to play a riboregulatory role and as an mRNA sequence encoding the functional peptide Fst, which jointly regulates biofilm formation.